Physical and mental health changes in the five years before and five years after childbirth: A population-based panel study in first-time mothers and fathers from Germany - Eva Asselmann; Susan Garthus-Niegel; Susanne Knappe; Julia Martini (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
Background: The transition to parenthood is characterized by far-reaching changes in life. However, little prospective-longitudinal evidence from general population samples exists on changes of general physical and mental health in the years around the birth of a child among mothers and fathers. Methods: Using data from the German Socio-Economic Panel Study (SOEP), this study examined continuous and discontinuous short- and long-term changes of general physical and mental health from five years before until five years after the birth of the first child in women (N = 1,912) and men (N = 1,742). Whether a child was born was assessed annually throughout the study. Physical and mental health was assessed biannually from 2002 to 2018 with the SF-12v2. Results: Multilevel analyses revealed that women experienced a considerable decrease of physical health during pregnancy, which remitted after delivery. On average, women's mental health increased in the last year before and first year after delivery. These mental health improvements were stronger in older vs. younger mothers and remained largely stable in the years after childbirth. In contrast, little evidence for changes of general physical or mental health in (expectant) fathers was found. Limitations: Physical and mental health was assessed with a short questionnaire only (SF-12v2). Conclusions: On average, women's mental health tends to improve before and after the birth of the first child. Men seem to be much less affected by the birth of a child than many previous studies suggest.
Keywords: 330; pregnancy; parenthood; well-being; psychopathology; prospective-longitudinal